THE EFFECT OF JOB INEQUITY, JOB FAIRNESS ON TURNOVER INTENTION WITH COMMITMENT EMPLOYEES AS MODERATING VARIABLES - Afifah, Nur; Syaharuddin, Syaharuddin; Bin sapa, Nasrullah (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to analyze and explain the influence of job insecurity on employee turnover intentions at PT. Bank Muamalat Indonesia KCU Makassar, the influence of job fairness on employee turnover intentions at PT. Bank Muamalat Indonesia KCU Makassar, the influence of job insecurity on turnover intentions with employee commitment as a moderating variable at PT. Bank Muamalat Indonesia KCU Makassar, the influence of job fairness on turnover intentions with employee commitment as a moderating variable at PT. Bank Muamalat Indonesia KCU Makassar. This study uses a quantitative research type with associative analysis. The population in this study were all permanent employees at PT. Bank Muamalat Indonesia TBK. Makassar Branch, totaling around 105 people. This study uses a saturated sample technique so that the sample is 105 people. The instrument in this study used a questionnaire distributed to respondents via Google Form. The results of this study indicate that job insecurity has a positive and significant effect on turnover intentions, job fairness has a negative and significant effect on turnover intentions, employee commitment weakens the effect of job insecurity on turnover intentions, employee commitment strengthens the effect of job fairness on turnover intentions.